Neuropsychological and psychopathological correlates of insight in persons with OCD - Saima Ahmed; Rajesh Kumar; Niska Sinha; Priya Kumar (Industrial Psychiatry Journal)
Background: Obsessive-compulsive disorder (OCD) is a chronic psychiatric disorder characterized by persistent, distressing obsessive thoughts and compulsive behaviors. In OCD, the level of insight is classified as good, poor, or absent. Poorer insight is associated with a more complex clinical presentation and a poorer prognosis. Aim: The aim of our research was to investigate the relationship between the level of insight in individuals with OCD and various neuropsychological and psychopathological factors. Materials and Methods: This cross-sectional study recruited a total of 100 participants diagnosed with OCD. The Brown assessment of beliefs scale (BABS) was used to evaluate the insight of the patients. Psychopathology was assessed using the Yale–Brown obsessive compulsive scale (YBOCS) and Hamilton depression rating scale (HDRS). Neuropsychological assessments included the Stroop test, digit span test, controlled oral word association (COWA) test, trail making test, and Wisconsin card sorting test. Results: The majority of the patients had good insight (54%), mild depression (48%), and moderate symptom severity (47%). Patients with poor insight had significantly higher scores on the YBOCS and HAM-D. They also performed significantly worse on the WCST and TMT-A. Patients with comorbid depression (mild/moderate) showed significantly poor performance on the WCST compared to those without depression. Conclusion: The findings of our study indicate that patients with poor insight exhibit more severe forms of OCD, display greater psychopathology, and show more pronounced neuropsychological dysfunction.